1998
DOI: 10.1046/j.1469-7580.1998.19210013.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and cytochemical evaluation of sepsis‐induced changes in the rat pulmonary intravascular mononuclear phagocytes

Abstract: Sepsis stimulates an increase in the number and activity of mononuclear phagocytes in systemic host-defence organs. The present study was conducted to define the ultrastructural and cytochemical characteristics of the mononuclear phagocytes that sequester in the lung microvasculature of septic rats. Fourteen rats were challenged with a single intraperitoneal injection of saline (0n5 ml\100 g), E. coli (2i10(\100 g) or glucan (4 mg\100 g), and euthanased 2, 4, or 7 d later. The lungs were inflation fixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Although it is accepted that monocytes/macrophages enter alveoli following a multistep paradigm that includes vascular margination and effacements, very little attention has been paid to the recruitment and functions of intravascular monocytes/macrophages in lung inflammation. Previously we have reported ultrastructural evidence that a single challenge with E. coli induces recruitment of PIMMs by 48 hr, followed by their disappearance at 96 hr (Singh et al, 1998). Now we have used light and electron microscopic immunocytochemistry to show that recruited PIMMs in the rat react with ED-1 antibody.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Although it is accepted that monocytes/macrophages enter alveoli following a multistep paradigm that includes vascular margination and effacements, very little attention has been paid to the recruitment and functions of intravascular monocytes/macrophages in lung inflammation. Previously we have reported ultrastructural evidence that a single challenge with E. coli induces recruitment of PIMMs by 48 hr, followed by their disappearance at 96 hr (Singh et al, 1998). Now we have used light and electron microscopic immunocytochemistry to show that recruited PIMMs in the rat react with ED-1 antibody.…”
Section: Discussionmentioning
confidence: 91%
“…We have previously shown that recruited PIMMs represent a transient population and their numbers peak at 48 hr in our model (Singh et al, 1998). To determine their contributions to lung inflammation, we challenged rats with E. coli LPS at 48 hr post-E. coli infection and compared lung inflamma- Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In species where PIMs are not found at birth, their appearance in the lung can be induced by different effects, for example stimulation with lipopolysaccharides (LPS) or infectious agents, or by changes in the general condition of the organism, such as the presence of hepatic cirrhosis, tumors, hematologic diseases or experimental ligation of the bile duct (12,13). Pulmonary induction of PIM cells in the lung was described in rats, mice, hamsters, rabbits, chicken, dogs and macaques (14)(15)(16).…”
Section: Pim Cells In Generalmentioning
confidence: 99%
“…The globular surface coat of PIMs, probably anchored via a glycosyl-phosphatidyl inositol anchor, complexes with blood-borne materials such as tracer particles and endotoxins and mediates their endocytosis (3,43,46). PIM colonization of the lung occurs either early after birth in some species (constitutive PIMs) (28,65), later upon stimulation with lipopolysaccharide (LPS) and bacteria, or in conditions such as cirrhosis (induced PIMs) (11,13,45). Of the animals tested, the orders Artiodactyla (pigs, sheep, goats, llamas, reindeer, water buffalo) and Perissodactyla (horse; Fig.…”
mentioning
confidence: 99%